Analisa Pengaruh Variasi Temperatur dan Holding Time pada Proses Pack Carburizing Baja ASTM A36 Terhadap Kekerasan, Struktur Mikro dan Laju Korosi - Muhammad Akmaluddin Burhani; Edi Santoso (Pusat riset dan Inovasi Nasional, 2026)
ASTM A36 steel has relatively low hardness and corrosion resistance, making surface treatment necessary to improve its material properties. This study aims to determine the effect of temperature and holding time variations in the pack carburizing process on the hardness, corrosion rate, and microstructure of ASTM A36 steel. The pack carburizing process was carried out using coconut shell charcoal as the carburizing medium with temperature variations of 850°C, 900°C, and 950°C and holding times of 20, 40, and 60 minutes, followed by quenching in distilled water. Hardness testing was conducted using the Rockwell B scale (HRB) method, corrosion rate testing was performed according to the ASTM G31 method, and microstructural observations were carried out using Scanning Electron Microscopy (SEM). The results showed that increasing the temperature and holding time improved the hardness and corrosion resistance of ASTM A36 steel. The highest hardness value was obtained at a temperature of 950°C with a holding time of 60 minutes, reaching 114.1 HRB. Microstructural analysis revealed the formation of a martensitic phase on the specimen surface after the carburizing process.